Water Mass Versus Sea Level Effects on Benthic Foraminiferal Oxygen Isotope Ratios in the Atlantic Ocean During the LGM. Issue 1 (30th January 2019) - Völpel, R.; Mulitza, S.; Paul, A.; Lynch‐Stieglitz, J.; Schulz, M.
Abstract: Depth transects of benthic foraminiferal oxygen isotopes from the Atlantic Ocean show that glacial‐interglacial changes are larger at deep (> ~2, 000 m) than at intermediate water levels. Our model results suggest that the smaller changes in the upper 1, 000 m of the water column are a result of the glacial sea level lowering of about 120 m, leading to warmer temperatures of around 1 °C and hence a smaller glacial‐interglacial stable oxygen isotope difference. In contrast, a shoaling of the water mass boundary to ~2, 000‐m water depth between the northern and southern source waters is caused by the expansion of a cold (close to the freezing point) southern source water in the abyssal ocean, increasing the oxygen isotope values of benthic foraminifera from the Last Glacial Maximum in the deep Atlantic. These two effects explain the different amplitudes of glacial‐interglacial stable oxygen isotope differences in the upper and deeper water column of the Atlantic Ocean. Key Points: Benthic δ 18 O glacial‐interglacial changes off north West Africa and in the west Atlantic Ocean were investigated with an ocean model Model results suggest smaller glacial‐interglacial δ 18 O differences around the thermocline layer due to glacial sea level lowering The expansion of cold southern source water during the LGM led to larger glacial‐interglacial δ 18 O differences in the deep Atlantic Ocean